Evaluation Of Knowledge And Understanding Of Obstacles Encountered When Administering Resuscitation Medications Among Nurses In Lahore, Pakistan - Alvi, Safia Abdul Raheem (2024)
Medication errors is one of the primary causes of patient morbidity and death, which has a serious adverse impact on the healthcare system. Nurses' lack of knowledge is thought to have a crucial role in drug administration errors that risk patient safety. The purpose of this study was to evaluate nurses' knowledge of administering resuscitation medications, identify the barriers they encounter while doing so, and explore if resuscitation medication errors are being reported by nurses. A cross-sectional study was conducted among licensed nurses working within public and private hospitals of Lahore city, recruited using a convenient sampling method. A pre-validated, self-administered questionnaire adapted from a previous study was used which consisted of five sections: socio-demographics data, nurses’ knowledge of resuscitation medications, obstacles encountered during resuscitation medications administration, self-evaluation and resuscitation error events and reporting barriers was used. The data were entered using SPSS version 27, where categorical variables, comparative analysis, and independent group tests variables were used. The research included 409 nurses in total. Of whom, 44.7% had insufficient knowledge of resuscitation medications, while 55.3% were reported to have adequate knowledge (score > 70%). Significantly greater knowledge was linked to higher age and experience (p 0.001), working in a public hospital (p = 0.032), and having ACLS training (p = 0.006).